Comparative study of post-growth annealing of Cu(hfac)2, Co2(CO)8 and Me2Au(acac) metal precursors deposited by FEBID - Puydinger dos Santos, Marcos Vinicius; Szkudlarek, Aleksandra; Rydosz, Artur; Guerra-Nuñez, Carlos; Béron, Fanny; Pirota, Kleber Roberto; Moshkalev, Stanislav; Diniz, José Alexandre; Utke, Ivo (Beilstein Journal of Nanotechnology, 2018)
Non-noble metals, such as Cu and Co, as well as noble metals, such as Au, can be used in a number modern technological applications, which include advanced scanning-probe systems, magnetic memory and storage, ferroelectric tunnel junction memristors, metal interconnects for high performance integrated circuits in microelectronics and nano-optics applications, especially in the areas of plasmonics and metamaterials. Focused-electron-beam-induced deposition (FEBID) is a maskless direct-write tool capable of defining 3-dimensional metal deposits at nanometre scale for above applications. However, codeposition of organic ligands when using organometallic precursors is a typical problem that limits FEBID of pure metal nanostructures. In this work, we present a comparative study using a post-growth annealing protocol at 100, 200, and 300 °C under high vacuum on deposits obtained from Co2(CO)8, Cu(II)(hfac)2, and Me2Au(acac) to study improvements on composition and electrical conductivity. Although the as-deposited material was similar for all precursors, metal grains embedded in a carbonaceous matrix, the post-growth annealing results differed. Cu-containing deposits showed the formation of pure Cu nanocrystals at the outer surface of the initial deposit for temperatures above 100 °C, due to the migration of Cu atoms from the carbonaceous matrix containing carbon, oxygen, and fluorine atoms. The average size of the Cu crystals doubles between 100 and 300 °C of annealing temperature, while the composition remains constant. In contrast, for Co-containing deposits oxygen release was observed upon annealing, while the carbon content remained approximately constant; the cobalt atoms coalesced to form a metallic film. The as-deposited Au-containing material shows subnanometric grains that coalesce at 100 °C, maintaining the same average size at annealing temperatures up to 300 °C. Raman analysis suggests that the amorphous carbonaceous matrix of the as-written Co, Cu and Au deposits turned into nanocrystalline graphite with comparable crystal sizes of 12–14 nm at 300 °C annealing temperature. However, we observed a more effective formation of graphite clusters in Co- than in Cu- and Au-containing deposits. The graphitisation has a minor influence on the electrical conductivity improvements of Co–C deposits, which is attributed to the high as-deposited Co content and the related metal grain percolation. On the contrary, electrical conductivity improvements by factors of 30 and 12 for, respectively, Cu–C and Au–C deposits with low metal content are mainly attributed to the graphitisation. This relatively simple vacuum-based post-growth annealing protocol may be useful for other precursors as it proved to be efficient in reliably tuning the electrical properties of as-deposited FEBID materials. Finally, a H2-assisted gold purification protocol is demonstrated at temperatures around 300 °C by fully removing the carbon matrix and drastically reducing the electrical resistance of the deposit.
Keywords: copper; gold; cobalt; focused-electron-beam-induced deposition; noble metal; non-noble metals; post-growth annealing

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Noh, J. H.; Stanford, M. G.; Lewis, B. B.; Fowlkes, J. D.; Plank, H.; Rack, P. D. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Botman, A.; Mulders, J. J. L.; Hagen, C. W. (Nanotechnology, 2009)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Puydinger dos Santos, M. V.; Velo, M. F.; Domingos, R. D.; Zhang, Y.; Maeder, X.; Guerra-Nuñez, C.; Best, J. P.; Béron, F.; Pirota, K. R.; Moshkalev, S.; Diniz, J. A.; Utke, I. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Bernau, L.; Gabureac, M.; Utke, I. (Angew. Chem., Int. Ed., 2010)

Nanofabrication using focused ion and electron beams: principles and applications - Utke, I.; Moshkalev, S.; Russel, P. (Oxford University Press, 2012)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Toth, M.; Lobo, C.; Friedli, V.; Szkudlarek, A.; Utke, I. (Beilstein J. Nanotechnol., 2015)

(untitled) - Wnuk, J. D.; Rosenberg, S. G.; Gorham, J. M.; van Dorp, W. F.; Hagen, C. W.; Fairbrother, D. H. (Surf. Sci., 2011)

(untitled) - Gabureac, M.; Bernau, L.; Utke, I.; Boero, G. (Nanotechnology, 2010)

(untitled) - Utke, I.; Luisier, A.; Hoffmann, P.; Laub, D.; Buffat, P. A. (Appl. Phys. Lett., 2002)

(untitled) - Kolb, F.; Schmoltner, K.; Huth, M.; Hohenau, A.; Krenn, J.; Klug, A.; List, E. J. W.; Plank, H. (Nanotechnology, 2013)

(untitled) - Huth, M.; Kolb, F.; Plank, H. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Schwalb, C. H.; Grimm, C.; Baranowski, M.; Sachser, R.; Porrati, F.; Reith, H.; Das, P.; Müller, J.; Völklein, F.; Kaya, A.; Huth, M. (Sensors, 2010)

(untitled) - Gabureac, M. S.; Bernau, L.; Boero, G.; Utke, I. (IEEE Trans. Nanotechnol., 2013)

(untitled) - Edinger, K.; Gotszalk, T.; Rangelow, I. W. (J. Vac. Sci. Technol., B, 2001)

(untitled) - Sqalli, O.; Utke, I.; Hoffmann, P.; Marquis-Weible, F. (J. Appl. Phys., 2002)

(untitled) - Winhold, M.; Weirich, P. M.; Schwalb, C. H.; Huth, M. (Appl. Phys. Lett., 2014)

(untitled) - Höflich, K.; Becker, M.; Leuchs, G.; Christiansen, S. (Nanotechnology, 2012)

(untitled) - Shawrav, M. M.; Belić, D.; Gavagnin, M.; Wachter, S.; Schinnerl, M.; Wanzenboeck, H. D.; Bertagnolli, E. (Chem. Vap. Deposition, 2014)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Belić, D.; Bertagnolli, E. (ACS Nano, 2013)

(untitled) - Fernández-Pacheco, A.; De Teresa, J. M.; Szkudlarek, A.; Córdoba, R.; Ibarra, M. R.; Petit, D.; O’Brien, L.; Zeng, H. T.; Lewis, E. R.; Read, D. E.; Cowburn, R. P. (Nanotechnology, 2009)

(untitled) - Sharma, N.; van Mourik, R. A.; Yin, Y.; Koopmans, B.; Parkin, S. S. P. (Nanotechnology, 2016)

(untitled) - Pablo-Navarro, J.; Magén, C.; de Teresa, J. M. (Nanotechnology, 2016)

(untitled) - Szkudlarek, A.; Vaz, A. R.; Zhang, Y.; Rudkowski, A.; Kapusta, C.; Erni, R.; Moshkalev, S.; Utke, I. (Beilstein J. Nanotechnol., 2015)

(untitled) - Belić, D.; Shawrav, M. M.; Gavagnin, M.; Stöger-Pollach, M.; Wanzenboeck, H. D.; Bertagnolli, E. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Belova, L. M.; Hellwig, O.; Dobisz, E.; Dan Dahlberg, E. (Rev. Sci. Instrum., 2012)

(untitled) - Utke, I.; Hoffmann, P.; Berger, R.; Scandella, L. (Appl. Phys. Lett., 2002)

(untitled) - Fernández-Pacheco, A.; Serrano-Ramón, L.; Michalik, J. M.; Ibarra, M. R.; De Teresa, J. M.; O’Brien, L.; Petit, D.; Lee, J.; Cowburn, R. P. (Sci. Rep., 2013)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Fowlkes, J. D.; Geier, B.; Lewis, B. B.; Rack, P. D.; Stanford, M. G.; Winkler, R.; Plank, H. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Mulders, J. J. L. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Sachser, R.; Reizh, H.; Huzel, D.; Winhold, M.; Huth, M. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Elbadawi, C.; Toth, M.; Lobo, C. J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Plank, H.; Noh, J. H.; Fowlkes, J. D.; Lester, K.; Lewis, B. B.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Shawrav, M. M.; Taus, P.; Wanzenboeck, H. D.; Schinnerl, M.; Stoger-Pollach, M.; Schwarz, S.; Steiger-Thirsfeld, A.; Bertagnolli, E. (Sci. Rep., 2016)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Microelectron. Eng., 2015)

(untitled) - Mansilla, C.; Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2016)

(untitled) - Roberts, N. A.; Fowlkes, J. D.; Magel, G. A.; Rack, P. D. (Nanoscale, 2013)

(untitled) - Roberts, N. A.; Gonzalez, C. M.; Fowlkes, J. D.; Rack, P. D. (Nanotechnology, 2013)

(untitled) - Stanford, M. G.; Lewis, B. B.; Noh, J. H.; Fowlkes, J. D.; Roberts, N. A.; Plank, H.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Weirich, P. M.; Winhold, M.; Schwalb, C. H.; Huth, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Henry, M. R.; Kim, S.; Fedorov, A. G. (J. Phys. Chem. C, 2016)

(untitled) - Walz, M.-M.; Schirmer, M.; Vollnhals, F.; Lukasczyk, T.; Steinrück, H.-P.; Marbach, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Shawrav, M. M.; Belic, D.; Wachter, S.; Waid, S.; Stoeger-Pollach, M.; Bertagnolli, E. (Chem. Vap. Deposition, 2014)

(untitled) - Muthukumar, K.; Jeschke, H. O.; Valentí, R.; Begun, E.; Schwenk, J.; Porrati, F.; Huth, M. (Beilstein J. Nanotechnol., 2012)

(untitled) - Porrati, F.; Sachser, R.; Walz, M.-M.; Vollnhals, F.; Steinrück, H.-P.; Marbach, H.; Huth, M. (J. Phys. D: Appl. Phys., 2011)

(untitled) - Rosenberg, S. G.; Barclay, M.; Fairbrother, D. H. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Wachter, S.; Gavagnin, M.; Wanzenboeck, H. D.; Shawrav, M. M.; Belić, D.; Bertagnolli, E. (Nanofabrication, 2014)

(untitled) - Pablo-Navarro, J.; Sanz-Hernández, D.; Magén, C.; Fernández-Pacheco, A.; de Teresa, J. M. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Córdoba, R.; Sharma, N.; Kölling, S.; Koenraad, P. M.; Koopmans, B. (Nanotechnology, 2016)

(untitled) - Esfandiarpour, S.; Boehme, L.; Hastings, J. T. (Nanotechnology, 2017)

(untitled) - Utke, I.; Hoffmann, P.; Dwir, B.; Leifer, K.; Kapon, E.; Doppelt, P. (J. Vac. Sci. Technol., B, 2000)

(untitled) - Fedorov, A. G.; Kim, S.; Henry, M.; Kulkarni, D.; Tsukruk, V. V. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Kulkarni, D. D.; Rykaczewski, K.; Singamaneni, S.; Kim, S.; Fedorov, A. G.; Tsukruk, V. V. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Tuinstra, F.; Koenig, J. L. (J. Chem. Phys., 1970)

(untitled) - Robertson, J. (Mater. Sci. Eng., R, 2002)

(untitled) - Ferrari, A. C.; Robertson, J. (Phys. Rev. B, 2000)

(untitled) - Cançado, L. G.; Takai, K.; Enoki, T.; Endo, M.; Kim, Y. A.; Mizusaki, H.; Jorio, A.; Coelho, L. N.; Magalhães-Paniago, R.; Pimenta, M. A. (Appl. Phys. Lett., 2006)

(untitled) - Ōya, A.; Ōtani, S. (Carbon, 1979)

(untitled) - Kulkarni, D. D.; Kim, S.; Fedorov, A. G.; Tsukruk, V. V. (Adv. Funct. Mater., 2012)

The Fischer–Tropsch Synthesis - Anderson, R. B. (Academic Press, 1984)